Association between factors related to family planning/sexual and reproductive health and contraceptive use as well as consistent condom use among internal migrant population of reproductive ages in three cities in China, based on Heckprobit selection models. Issue 11 (13th November 2018) - Xu, Shuang-Fei; Wu, Jun-Qing; Li, Yu-Yan; Yu, Chuan-Ning; Zhao, Rui; Zhou, Ying; Li, Yi-Ran; Zhang, Jun-Guo; Jin, Meng-Hua
Abstract : Objective: With the increased population mobility and the transition in population policy, scholars are quite concerned about family planning/sexual and reproductive health (SRH) and related factors among internal migrant population of reproductive age. Therefore, the proposed study was designed to explore the association between factors related to family planning/SRH and contraceptive use as well as consistent condom use among the above-described population in China. Design: Cross-sectional study. Setting: Three municipalities in China, namely Beijing, Shanghai and Chongqing. Participants: Among the 6545 participants, 2099, 2414 and 2031 subjects came from Beijing, Shanghai and Chongqing, respectively. Results: A total of 6545 eligible participants were included as the full sample, 6188 of whom who had intercourse in the last 3 months were selected as the subsample. Among the subsample, 80.88% (5005/6188) adopted any form of contraceptive methods and 49.14% (3041/6188) consistently used condom in the last three sexual intercourses. Meanwhile, the involved participants had a better mastery of knowledge on SRH than on contraception (p<0.0001). The results of the Heckprobit models revealed that the factors associated with both contraceptive use and consistent condom use were relationship with the first intercourse partner, communication frequency with spouse/sexual partners on sex, actual number of children and knowledge on SRH, while knowledge on contraception and age at first intercourse were associated with contraceptive use and consistent condom use, respectively (p<0.05). Conclusions: In the current study, we revealed a high-level contraceptive prevalence, a relatively low-level consistent condom use and a poor mastery of knowledge on contraception and SRH. The Heckprobit selection model specified the existence of selection bias, providing evidence on the association between the factors on family planning/SRH and contraceptive use as well as consistent condom use, respectively. Our findings indicated that health institutions should offer appropriate technology and high-quality family planning/SRH services for the internal migrant population in China.